Pelatihan IT Berstandar Global Menggunakan Platform GMetrix Bagi Mahasiswa Semester Akhir Universitas PGRI Madiun - Sekreningsih Nita; Andria Andria; Kelik Sussolaikah; Aurisha Lutvinda Putrian (Universitas Kristen Indonesia Toraja, 2024)
In the era of technology, it requires everyone to always be ready to utilize all technology-based media for both work and communication. Especially for academics, in last semester students at Universitas PGRI Madiun to produce graduates who are smart, competitive and have entrepreneurial skills. To achieve this mission, before graduating, students are equipped with skills in understanding competencies in the field of information technology with training and IT competency tests using the GMetrix and Certiport platforms as internationally recognized exam service provider portals in the IT field. The team uses blended methods for implementing this service activity. The final result of this IT training and mentoring activity was that 80% of the total + 1039 participants successfully passed with a very good score of 700-800 and a minimum passing point of 700. Proof of graduation is in the form of an international standard certificate in the IT field.